Alinhamento construtivo em um currículo por competências para engenharia mecânica: percepção de docentes - Mainginski, Fábio Edenei (2019)
This study was carried out in the Graduate Studies Program in Science and Technology Teaching at the Federal Technological University - Paraná (Universidade Tecnológica Federal do Paraná), at the Ponta Grossa campus and its theme was continuing education. The research objective is to analyse, in the perception of the representatives of the Structuring Teacher Nucleus and of the mechanical engineering Coordinator, how the course design workshop, conducted according to the fundamentals of the constructive alignment theory, influences the state of awareness, motivation and aptitude of its participants for the development of a pedagogical course project based on competences, in comparison with their peers who didn‟t participate in the same workshop. The analysis is based mainly on the studies of Anderson (2011), Biggs (2011), Mendonça (2015), Moran (2018), Moraes (2003), Perrenoud (1999), (2000), (2001), Scallon (2015) and Zabala (2014). The methodological approach of the research is qualitative, empirical and based on the discursive textual analysis. The empirical study was carried out through semistructured interviews with the participation of a group of specialist teachers which were members or were linked to the Structuring Teacher Nucleus of the course. They were separated in two groups: those who participated in the workshop and those who didn‟t. In teachers' perception, motivation was shown in both groups‟ reports for the construction of a pedagogical project based on competences. There was no perceived framework in the states of awareness and aptitude among the teachers of the group that didn‟t participate in the workshop. On the other hand, the course design workshop allowed its participants to reach higher mental processes, specifically, in Anderson's classification (2001): application, analysis, evaluation and creation, leading this group of teachers to indicate paths to be followed for the development of a program that changes the curricular structure of the course with a competence approach.